2019
DOI: 10.1103/physrevlett.122.218102
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Slow Stress Relaxation in the Cytoskeleton

Abstract: Dynamically crosslinked semiflexible biopolymers such as the actin cytoskeleton govern the mechanical behavior of living cells. Semiflexible biopolymers nonlinearly stiffen in response to mechanical loads, whereas the crosslinker dynamics allow for stress relaxation over time.Here we show, through rheology and theoretical modeling, that the combined nonlinearity in time and stress leads to an unexpectedly slow stress relaxation, similar to the dynamics of disordered systems close to the glass transition. Our w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 52 publications
10
59
0
Order By: Relevance
“…Here, we can confirm that the source of the pre-stress responsible for low β values of the cortex of living cells are indeed myosin motors. In the absence of motor activity and therefore low pre-stress T 0 , β peaks around ≈ 0.5 − 0.6 as theoretically expected for reversibly cross-linked actin filaments [17] reflecting the broad spectrum of relaxation times from the unbinding and rebinding of various crosslinkers. However, at larger pre-stress the network indeed solidifies as predicted by Koenderink and coworkers [17].…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Here, we can confirm that the source of the pre-stress responsible for low β values of the cortex of living cells are indeed myosin motors. In the absence of motor activity and therefore low pre-stress T 0 , β peaks around ≈ 0.5 − 0.6 as theoretically expected for reversibly cross-linked actin filaments [17] reflecting the broad spectrum of relaxation times from the unbinding and rebinding of various crosslinkers. However, at larger pre-stress the network indeed solidifies as predicted by Koenderink and coworkers [17].…”
supporting
confidence: 63%
“…We found that an increase in internal stress due to higher myosin activity is accompanied by a reduction of the power law coefficient (Fig. 3B) suggesting that cells with a stiffer, more [17] suggesting that the glassy dynamics of the cortex are a natural consequence of transient cross-links combined with intrinsic pre-stress. Here, we can confirm that the source of the pre-stress responsible for low β values of the cortex of living cells are indeed myosin motors.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Weak catch bonds make strong networks Yuval Mulla 1,2 , Mario J Avellaneda , Antoine Roland 1 , Lucia Baldauf 1,3 , Sander J Tans 1,3 *, Gijsje H Koenderink 1,3 *…”
Section: Extended Data Figuresmentioning
confidence: 99%
“…1. Catch bond 7 linkers in low tension areas rapidly unbind, increasing the pool of unbound linkers(2). As a result, there is increased binding everywhere in the network (3), at the expense of only the linkers in low tension areas.…”
mentioning
confidence: 99%